PENGARUH E-WOM, PENGETAHUAN PRODUK, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN IPHONE BEKAS BERGARANSI EX INTERNASIONAL DI PONOROGO - Aropah, Dimas Zainatul; Wijayanto, Heri; Wahyuningsih, Dwi Warni (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine the Influence of E-WOM, Product Knowledge, and Lifestyle on the Decision to Purchase a used Iphone with an Ex International warranty in Ponorogo. The method used in this study is a quantitative method. The data from this study were obtained through distributing questionnaires with written statements to respondents and analyzed using the SPSS 21 software application. The population in this study were Iphone users with Ex International warranty in Ponorogo. The sample in this study amounted to 100 using the Simple Random Sampling technique. The results of this study indicate that: (1) There is an influence between e-wom on the decision to purchase a used Iphone with an Ex International warranty in Ponorogo. (2) There is an influence between product knowledge on the decision to purchase a used Iphone with an Ex International warranty in Ponorogo. (3) There is an influence between lifestyle on the decision to purchase a used Iphone with an Ex International warranty in Ponorogo. (4) There is an influence between e-wom, product knowledge, and lifestyle on the decision to purchase a used Iphone with an Ex International warranty in Ponorogo